PENGARUH NAA DAN BAP TERHADAP PERTUMBUHAN CIPLUKAN (Physalis angulate L.) SECARA IN-VITRO - Amri Assidiqi; Hasan Basri Jumin; Ernita (UIR Press, 2018)
ABSTRACT The purpose of this study was to determine the interactions and main effects of NAA and BAP hormones on the growth of Ciplukan (Physalis angulata L.). The design used in this study is a complete random design (CRD) which consists of two factors. The first factor is N (NAA) which consists of 4 levels, namely: without treatment, 0.1, 1, and 10 mg / l while the second factor is B (BAP) consisting of 4 levels, namely: without treatment, 0.1, 1 and 10 mg / l. The parameters observed were the percentage of hypocotyl explants forming callus, the age of callus appearing, the number of shoots, and the percentage of hypocotyl explants forming roots. The observational data is then statistically analyzed, if the F count is greater than the F table then proceed with the BNJ test at the 5% level. The results showed that the interaction of NAA and BAP gave a significant effect on the age of callus with the best treatment was the administration of 0.1 mg / l NAA and mg / l BAP 1 (N1B2). The main effect of NAA was significantly on the age of callus with the best treatment of 1 mg / l NAA (N2). The main effect of BAP was significantly on the age of callus with the best treatment 1 mg / l BAP (B2) and the percentage of hypocotyl explants forming roots with the best treatment without BAP administration (B0). Keywords: Ciplukan, NAA, BAP